Computational investigation of boiling flows within micro-pin fin evaporators for thermal management of high-power density micro-electronics - El Mellas, Ismail (2024)
Recent advancements in micro-manufacturing and microelectronic technologies have enabled the large-scale production of high-power-density devices, such as fuel cells, batteries, and electronic chips. The exponential growth in the power output of these devices has created a compelling need for efficient cooling systems. Traditional single-phase cooling systems, typically limited to heat fluxes of less than 1 MW/m2 , are illequipped to handle the substantial heat fluxes, often on the order of several MW/m2, generated by these high-power devices [1]. In contrast, multiphase flows with phase change offer viable technological solutions, allowing for the dissipation of additional heat in the form of latent heat. Boiling flows maintain uniform surface temperatures, a critical factor in the proper functioning of components, and can respond positively and passively to localised hot spots as the heat transfer coefficient increases with heat flux. One promising technology in this regard is the use of pin-fin micro-evaporators, which, compared to conventional straight channels, have the added advantage of disrupting the flow field. This promotes flow mixing, enhances the local surface area, and increases the local heat transfer coefficient, ultimately leading to improved thermal and hydraulic performance. Despite numerous experimental studies on boiling heat transfer in micro-pin fins, ongoing debates persist regarding the underlying dynamics. This is partly due to the limitations of existing experimental techniques, which cannot provide sufficient resolution to investigate the small spatial and temporal scales of the flow. In this study, a comprehensive numerical investigation of two-phase flows propagating through arrays of pin-fins is presented. The study comprises two main parts: one conducted under adiabatic conditions and the other under diabatic conditions. The simulations were performed via the Volume of Fluid (VOF) method implemented in OpenFOAM. Various conditions relevant to heat exchangers for industrial applications were tested, including low-viscosity fluids (e.g., water, refrigerants), laminar flows, and uniform heat loads of hundreds of kW/m2 . Different configurations of the obstacles were also tested in the investigation. The thesis aims to unveil the dynamics of two-phase flow propagating across micro-pin fin arrays and, more generally, non-straight channels, with a focus on understanding how the flow is affected by the pin-fins. This involves studying bubble behaviour, the size and morphology of the liquid film, and heat transfer performances. The simulations reveal that the dynamics of two-phase flows through pin-fins differ significantly from those observed in straight channels. As bubbles traverse the arrays of pin-fins, the pin walls tend to be covered, and lateral extension occurs in the gap between adjacent obstacles. The shape of the bubbles and the morphology of the liquid film are directly linked to the pin shape, resulting in entirely different outcomes. Heat transfer performances are significantly influenced by the initialisation spot of the bubbles; generally, higher performances are observed when the bubble nucleates in a downstream region where the fluid is stagnant, leading to the generation of multiple bubbles and coverage of a larger surface area by the two-phase flow.